Pendidikan Karakter Berbasis Kearifan Lokal - St. Mislikhah (STAIFAS-Press, 2020)
The current phenomenon shows that the noble character values ​​among children are experiencing a quite concerning crisis. One of the factors causing the deterioration of children's character is a crisis or deterioration of national cultural values ​​or local wisdom values. Therefore, exploring cultural values ​​or local wisdom values ​​is a strategic step in an effort to build the nation's character. The purpose of this study was to describe (1) character education through traditional games in MIN 3 Jember, (2) character education through traditional songs in MIN 3 Jember, and (3) character education through folklore in MIN 3 Jember. To achieve this goal, this study uses a phenomenological type of qualitative approach. The data collection technique uses observation, interview, and documentary study techniques. The data collected are primary data and secondary data which include: character education strategy data through traditional games, character education through traditional songs, and character education through folk stories. After the data is collected, it is analyzed using themodel spiral analysis proposed by Cresswel (2007). The results showed that (1) The teachers at MIN 3 Jember have used traditional games as a medium to instill character values ​​in students. The traditional games played by students are quite varied. The steps taken by the teacher in using traditional games as a medium in instilling the character of students are: choosing traditional games that are in accordance with the learning theme, playing games together with students, followed by explaining the character values ​​contained in the games that have been played the. (2) Teachers at MIN 3 Jember have used traditional songs as a medium to instill character values ​​in students. The steps taken by the teacher in using traditional songs as a medium to instill the character of students, namely: choosing traditional songs that are in accordance with the learning theme, singing songs together with students, followed by explaining the character values ​​contained in traditional songs that have been sung. (3) teachers at MIN 3 Jember have used folklore as a medium to instill character values ​​in students. The steps taken by the teacher in using folklore to instill character values ​​are: (a) the children read the folklore in groups or independently, (b) to find out whether the children understand the story, the teacher make inquiries via 5W + H. (c) the teacher retells the folklore to the children, and (d) the teacher conveys the messages (character values) that exist in the story.